2001
DOI: 10.1002/app.1217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recycled polypropylene on polypropylene/high‐density polyethylene blends

Abstract: ABSTRACT:The effect of recycled PP on incompatible blends of virgin polypropylene (PP) and high-density polyethylene (HDPE) was studied. Recycled PP from urban solid waste was extracted with methyl ethyl ketone and the compatibilizing action of the product before and after extraction was examined. The characterization of the recycled PP was performed by FTIR, NMR, and DSC analyses. Mechanical properties of the blends were evaluated. The results showed partial compatibility of the blend components, reflected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 3 publications
1
19
0
1
Order By: Relevance
“…La energía absorbida por la influencia del calor, luz, etc estrés mecánico, la rotura causa de enlaces CH de los servicios de carbono, que tienen vínculos más débiles que los otros carbones, lo que genera radicales libres que son capaces de reaccionar con el oxígeno para formar peróxidos e hidroperóxidos, que a su vez producen más radicales libres resultantes de la división de cadenas [19][20][21][22] . El PP puede presentar varios grupos cromóforos (grupos generadores de radicales libres) como iniciadores de la degradación del PP que inducen a la ruptura de la cadena.…”
Section: Resultados Y Conclusionesunclassified
“…La energía absorbida por la influencia del calor, luz, etc estrés mecánico, la rotura causa de enlaces CH de los servicios de carbono, que tienen vínculos más débiles que los otros carbones, lo que genera radicales libres que son capaces de reaccionar con el oxígeno para formar peróxidos e hidroperóxidos, que a su vez producen más radicales libres resultantes de la división de cadenas [19][20][21][22] . El PP puede presentar varios grupos cromóforos (grupos generadores de radicales libres) como iniciadores de la degradación del PP que inducen a la ruptura de la cadena.…”
Section: Resultados Y Conclusionesunclassified
“…In this case the properties of the recycled blends are suitable to applications requiring good mechanical performances, but, of course, the costs of the operation are higher. Actually, an attempt was made (Bonelli et al 2001) to compatibilize the blend with r-PP extracted by floatation. It was found that PP exposed to random/noncontrolled outdoor conditions provided spontaneous non-oxidative chemical modifications that brought a certain compatibilization action to the PE/PP blends.…”
Section: With Polymers Different From the Recycled Onementioning
confidence: 99%
“…The resultant governing equations obtained by theoretical treatments of such conjugated Graetz problems could be solved analytically by means of orthogonal expansion techniques [11,12]. The heat transfer enhancement in one or more flowing streams has attracted a great deal of interest in recent years because of the wide use of recycle effect in chemical processes and food industries such as distillation [13], extraction [14], adsorption [15], mass diffusion [16], thermal diffusion [17], loop reactors [18], air-lift reactor [19] and draft-tube bubble column [20].…”
Section: Introductionmentioning
confidence: 99%